PENGEMBANGAN MINAT BELAJAR SEBAGAI SARANA UNTUK MENINGKATKAN KONSENTRASI BELAJAR DENGAN ADANYA PENGARUH MEDIA SOSIAL DAN LINGKUNGAN - Siti Najia Humaida; Raihana; Hairuning Suci Anggela (LPPM Universitas Awal Bros, 2024)
This study aims to determine the effect of environment, use of social media, and interest on student learning concentration at SMK PGRI. This study uses a qualitative approach with a survey type of research, with the data collection technique using a questionnaire instrument, the research subject is done with the Random Sampling Technique, totaling 48 students. Data analysis techniques using Structural Equation Modeling (SEM) using smartPLS tools. The results of the study the environment has a positive and significant effect on student learning concentration, social media has a negatif and insignificant effect on learning concentration and interest has a significant positive effect on the concentration of learning of XII grade students of SMA PGRI Pekanbaru.